1999
DOI: 10.1046/j.1365-3156.1999.00468.x
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological features and case management practices of imported malaria in northern Italy 1991–1995

Abstract: SummaryWe report the results of a retrospective analysis of the clinical charts of imported malaria cases notified during the period 1991-95 in the Lombardy region of northern Italy. We analysed 694 admissions related to 683 individuals. The proportion of immigrants increased during the observation period from 34.4% in 1991 to 59.9% in 1995 (P ϭ 0.002). P. falciparum was the causative species in 534 cases (78.2%), and 591 (90.1%) of 656 cases with a full travel history had travelled to Africa. Information on c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
27
1
2

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 6 publications
6
27
1
2
Order By: Relevance
“…A retrospective study that had been conducted at The University Hospital in Heidelberg, Germany and included 122 patients with falciparum malaria, showed that thrombocytopenia was a significant predictor of severe malaria [21]. These findings were corroborated by other authors [20,38]. In severe malaria, the concentrations of proinflammatory cytokines such as TNF-α, IL-1, IL-6, and IL-12 are elevated [39].…”
Section: Discussionsupporting
confidence: 52%
“…A retrospective study that had been conducted at The University Hospital in Heidelberg, Germany and included 122 patients with falciparum malaria, showed that thrombocytopenia was a significant predictor of severe malaria [21]. These findings were corroborated by other authors [20,38]. In severe malaria, the concentrations of proinflammatory cytokines such as TNF-α, IL-1, IL-6, and IL-12 are elevated [39].…”
Section: Discussionsupporting
confidence: 52%
“…Use of chemoprophylaxis is recommended for all children who travel to high-risk malaria-endemic areas (34). Several studies have indicated, however, that correct use of and adherence to chemoprophylaxis is low (13,16,(35)(36)(37)(38).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have been conducted in semi-immune children in endemic areas to improve the diagnosis of malaria in the absence of microscopy, [22][23][24][25][26][27] but their conclusions are not readily applicable to nonimmune travelers returning from the tropics with fever. From the purely descriptive studies in nonimmune travelers or migrants, [6][7][8][9][10][11][12][13][14][15] we expected inadequate prophylaxis, measured fever, enlarged spleen, and thrombopenia to be important predictors of malaria. These parameters were confirmed in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Reports on imported malaria generally describe the clinical presentation of hospitalized patients in centers that specialized in tropical medicine, [6][7][8][9][10][11][12][13][14][15] although no study was specifically designed to estimate the predictive values of the different clinical characteristics. One study in Canada investigated retrospectively whether the clinical presentation or the laboratory parameters could be used for predicting malaria infection in febrile travelers.…”
Section: Introductionmentioning
confidence: 99%